Rethinking poverty, power and privilege: A feminist post-structuralist research exploration - Hulme, Thérèse (HTS teologiese studies, 2012)
In this article, I described how the use of feminist methodology and post-structuralist analyses of the experiences of women in a poor ‘Coloured’ community in my research led to new understandings of the experiences of poverty and privilege. I discovered the relevance of Foucault’s historical analysis of the operation of ‘pastoral power’ through the narratives of women from the Scottsville community. Historical and current accounts of so-called ‘Coloured’ women’s subjugation and categorisation are reminders of how it came about that ‘being Coloured’ became associated in South Africa with shame and with ‘knowing one’s place’. Feminist post-structuralist analyses made visible the conditions that created practices of injustice in poor women’s lives whilst, at the same time, creating conditions of privilege for me. Justice-making in Scottsville therefore started with a radical rethinking of the terms by which people’s marginalisation took place and, consequently also of the terms of ‘just’ cross-cultural engagements.